Gallstone-related abdominal cystic mass presenting 6 years after laparoscopic cholecystectomy: A case report. (2017) - Faour, Rama; Sultan, Dana; Houry, Rand; Faour, Mhamad; Ghazal, Ahmad
Highlights: Laparoscopic cholecystectomy (LC) is the gold standard for gallbladder disease. Complications of gallstones spillage in the peritoneum are uncommon. We report a case of spilled gallstones presenting 6 years after LC with uncharacteristic clinical presentation. The diagnosis of gallstone abscess after years of LC is usually a diagnostic challenge. Abstract: Introduction: Although gallbladder perforation and gallstones spillage are common complications during laparoscopic cholecystectomy (LC), clinically significant complications resulting from stones left in the peritoneum are extremely uncommon. We report a rare case of spilled gallstones complication with a late and uncharacteristic presentation. Presentation of the case: A 44-year-old Caucasian female presented with a complaint of a mass in the right upper quadrant associated with a cramping pain for the last 6 months. Her past surgical history included a laparoscopic cholecystectomy performed six years ago. Abdominal computed tomography demonstrated an intra-abdominal cystic mass. On open exploration, a cystic mass adhered to the abdominal wall was excised containing two gallstones. The patient tolerated the procedure well and had uneventful postoperative recovery. Discussion: Although unretrieved gallstones are considered harmless, serious complications can occur early or late. The most frequent complication is the formation of abscesses in different locations. Conclusion: The diagnosis of gallstone abscess after years of LC is usually a diagnostic challenge. Obtaining a comprehensive past surgical history still plays an important role in the assessment of patients presenting with unusual findings.